Topography Wetness Index Application in Flood-Risk-Based Land Use Planning - Pourali, S. H.; Arrowsmith, C.; Chrisman, N.; Matkan, A. A.; Mitchell, D. (Applied spatial analysis and policy, 2016)
Land use planners and drainage engineers require, among other information, a clear map that delineates land subject to flash flooding before they can approve residential development. Through the application of spatially distributed models, the topographic wetness index (TWI) can be determined as an alternative to the traditional approach of delineating flood-prone areas using contours alone. The TWI provides a more cost-efficient approach to flood determination than conventional hydrodynamic models. This paper describes an application of the TWI approach to a flood-prone study area in the town of Inverloch, Victoria, Australia. The TWI proved useful in the early stages of land use planning for residential development in Inverloch.